Design and implementation of an error detection and correction method compatible with MODBUS-RTU by means of systematic codes. (September 2016) - Urrea, Claudio; Morales, Claudio; Muñoz, Rodrigo
Highlights: An error detection and correction scheme for MODBUS-RTU networks is presented. The proposed scheme respects the parameters of the MODBUS-RTU protocol. The tests carried out show their effectiveness to improve the transmission quality. Abstract: The design and implementation of an error detection and correction scheme in a MODBUS-RTU network based on the REED-SOLOMON code is presented. The transmission of the parity bits is made respecting the parameters of the MODBUS protocol, so the bus can be used by common devices without the error detection/correction scheme. The error detection–correction is performed by means of specialized repeating devices in the receiver and transmitter. This method respects the parameters of the MODBUS-RTU protocol, so the bus enhanced with retransmitter devices can be used along with common devices. Finally, the implementation of an experimental network is described and the practical results obtained are given.